PENGARUH RASIO DAGING AYAM BROILER (Gallus domesticus) DENGAN JAMUR MERANG (Volvariella volvacea S.) TERHADAP KARAKTERISTIK TUM AYAM - Rahmadaeni, Kiki Iqlima; Suter, I Ketut; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
The aims of this research was to determine the effect of the ratio of broiler chicken meat with straw mushroom to the characteristics of chicken tum and to determine the right comparison between chicken meat and straw mushroom that can produce chicken tum with the best characteristics. This study used a Completely Randomized Design with a treatment ratio between meat of broiled chicken and mushroom 100:0, 90:10, 80:20, 70:30, 60:40, and 50:50. This treatment was repeated 3 times so that was obtained as many as 18. Experimental units data were analyzed with Analysis of Variance (ANOVA) and then followed by Duncan's test. The ratio of  broiler chicken and straw mushroom significantly influenced texture, color hedonik, fat content and crude fiber content. Not significant effect to taste hedonic, flavor hedonic, overall hedonic and cholesterol content. The best treatment was 50% of broiler chicken meat with 50% straw mushroom , with the characteristic of chicken tum the analysis of fat content 9,33%, crude fiber content 11,16%, cholesterol content 2,22%, the texture, color, taste, flavor and overall were acceptance.   Keyword : chicken tum, straw mushrooms, fiber contetnt, fat contetnt.